The rise, fall and revival of the Papua New Guinea coffee industry - Sengere, Reuben Wanobo (Curtin University, 2016)
The PNG coffee industry expanded rapidly in the 1960s and 1970s and PNG produced high quality coffee. However, production began to stagnate in the 1990s and quality fell with the contraction of extension services and the decline of the plantation sector. In cooperatives and group-owned businesses, leadership was vital for effective management and governance, while in the managed subsector, the capacity of managers to embed their businesses in the local socio-economy was a factor in their sustainability. For smallholders, collective action, value chain partnerships and agro-services helped raise productivity and the quality of coffee.